Monkeypox is Now a Public Health Emergency of International Concern - Sharma, Prakash (Nepal Journal of Medical Sciences, 2022)
Monkeypox is a viral zoonosis caused by an orthopoxvirus. Although monkeypox and smallpox share many clinical features, monkeypox is generally less severe than smallpox. Recently, we have been encountering monkeypox outbreaks outside the non-endemic countries. WHO has now declared the global monkeypox outbreak as a public health emergency of international concern. Surveillance and rapid identification of new cases is the key step for outbreak containment.